(3YLGFH GdeNdhbGJ hZQGFH GdehLhOGJs - (3RcQjG Hf eMeO Hf eMehO,GdnbrRphjfj, CHh jMji YeGO GdOjf,J (B682 (3g` s ((3GHf ceGd GdOjf MSjf s)
(3ChdgG (B:s
(3ebQQ GdCQV hegOgG dCfhGY GdMjhGf s
(3BNQgG (B:s
(3Je gPG GdcJGH GdoeSei HYLGFH GdeNdhbGJ hZQGFH GdehLhOGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B183s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1127s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs